Comparative Transcriptome Profiling Reveals Coding and Noncoding RNA Differences in NSCLC from African Americans and European Americans - Mitchell, Khadijah A.; Zingone, Adriana; Toulabi, Leila; Boeckelman, Jacob; Ryan, Bríd M. (Clinical cancer research, 2017)
Purpose: To determine whether racial differences in gene and miRNA expression translates to differences in lung tumor biology with clinical relevance in African Americans (AAs) and European Americans (EAs). Experimental Design: The NCI-Maryland Case Control Study includes seven Baltimore City hospitals and is overrepresented with AA patients (∼40%). Patients that underwent curative NSCLC surgery between 1998 and 2014 were enrolled. Comparative molecular profiling used mRNA (n = 22 AAs and 19 EAs) and miRNA (n = 42 AAs and 55 EAs) expression arrays to track differences in paired fresh frozen normal tissues and lung tumor specimens from AAs and EAs. Pathway enrichment, predicted drug response, tumor microenvironment infiltration, cancer immunotherapy antigen profiling, and miRNA target enrichment were assessed. Results: AA-enriched differential gene expression was characterized by stem cell and invasion pathways. Differential gene expression in lung tumors from EAs was primarily characterized by cell proliferation pathways. Population-specific gene expression was partly driven by population-specific miRNA expression profiles. Drug susceptibility predictions revealed a strong inverse correlation between AA resistance and EA sensitivity to the same panel of drugs. Statistically significant differences in M1 and M2 macrophage infiltration were observed in AAs (P < 0.05); however, PD-L1, PD-L2 expression was similar between both. Conclusions: Comparative transcriptomic profiling revealed clear differences in lung tumor biology between AAs and EAs. Increased participation by AAs in lung cancer clinical trials are needed to integrate, and leverage, transcriptomic differences with other clinical information to maximize therapeutic benefit in both AAs and EAs. Clin Cancer Res; 23(23); 7412–25. ©2017 AACR.